2018
DOI: 10.1111/irv.12545
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with influenza vaccination among healthcare workers in acute care hospitals in Canada

Abstract: BackgroundInfluenza vaccine coverage rates among healthcare workers (HCWs) in acute care facilities in Canada remain below national targets.ObjectiveTo determine factors associated with influenza vaccine uptake among HCWs.MethodsThis secondary analysis of a prospective cohort study included HCWs aged 18‐69 years, working ≥20 h/wk in a Canadian acute care hospital. Questionnaires were administered to participants in the fall of the season of participation (2011/12‐2013/14) which captured demographic/household c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
2
5
0
1
Order By: Relevance
“…Another finding in our study illustrated that a previous history of immunization was positively correlated with the influenza vaccine uptake in the participants of this survey (p < 0.001), which is highly consistent with the results of many studies [10,23,[39][40][41].…”
Section: Discussionsupporting
confidence: 92%
“…Another finding in our study illustrated that a previous history of immunization was positively correlated with the influenza vaccine uptake in the participants of this survey (p < 0.001), which is highly consistent with the results of many studies [10,23,[39][40][41].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, this hypothesis is corroborated by a 2017 study carried out in a South Korean tertiary hospital [ 31 ] that also showed that individual, person-to-person awareness-raising was associated with an increased vaccination coverage rate among physicians only. A range of studies have shown the need to provide specific messages adapted to different professional groups as each category has different representations of, and attitudes towards, seasonal influenza vaccination [ 23 , 24 , 32 ]. With this in mind, future research should examine how to differentiate awareness-raising according to the specific target audiences taking part in pre-employment health checks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that years of work, departments of work, workplace regulations and access to free vaccination can be associated with influenza vaccinecoverage. [10][11][12] Besides, other researches have shown that the views of HCWs on the benefits, effectiveness, and side effects of influenza vaccine could affect their vaccineuptake. 13,14 The content of our questionnaire includes occupations, work departments, influenza vaccination status, reasons for vaccination receipt/non-receipt,workplace regulation, vaccination policy, etc.…”
Section: Methodsmentioning
confidence: 99%